(untitled) (American Journal of Islam and Society, 2001)
A manuscript of Al-Mawardi’s important political work Tashil al-Nadar (Facilitating -Administration) has recently been published. Examining this work, it appears that beyond the stereotype, conformist, Abbasid-patronized writer, there is another Mawardi. Hence, an attempt is made in this article to show that some of Al-Mawardi’s major ideas in political theory have not been seriously studied by any of the modem scholars who write on Islamic medieval political thought - most of whom have not even seen al-Mawardi’s Tashil al-Nadar. I will argue, moreover, that what has been left out of al-Mawardi’s works is probably more relevant to political theory, and that some conclusions arrived at in works that have become classics in the field are not well founded.